Management of cervical monoradiculopathy due to prolapsed intervertebral disc, an institutional experience - Amresh S Bhaganagare; S A Nagesh; B G Shrihari; Vikas Naik; M N Nagarjun; Balaji S Pai (Journal of Craniovertebral Junction and Spine, 2017)
Background: Cervical radiculopathy is the common clinical entity, often caused by “wear and tear” changes that occur in the spine. In the younger population, cervical radiculopathy is a result of a disc herniation or an acute injury causing foraminal impingement of an exiting nerve, whereas in the older individuals, it is due to foraminal narrowing from osteophyte formation, decreased disc height, and degenerative changes of the uncovertebral joints anteriorly and of the facet joints posteriorly. In most (75%–90%), cervical radiculopathy responds well to conservative treatment, whereas the remaining patients, who fail to achieve acceptable recovery with conservative modalities, alone need surgical decompression of the nerve root. Surgical interventions can be categorized into anterior and posterior approaches to the spine. Our study is focused on the surgical outcome of anterior discectomy with fusion versus posterior cervical discectomy with foraminotomy for cervical monoradiculopathy. Materials and Methods: Ours is a retrospective study including patients of one level unilateral posterolateral cervical disc prolapse with radiculopathy operated in Department of Neurosurgery, Bangalore Medical College and Research Institute between 2012 and June 2016. The hospital records, imagings, operation notes, and follow-up records were reviewed and analyzed. One hundred and fourteen patients of cervical monoradiculopathy were investigated and operated, 76 operated by anterior cervical discectomy with fusion (ACDF), and 38 operated by posterior cervical laminoforaminotomy (PCL). Results: The average operation time in 76 patients of ACDF group was 178 min and in 38 patients of PCL group was 72 min. Sixty-nine (91%) patients of ACDF and 38 (100%) patients of PCL had symptomatic relief but statistically (P > 0.5) was not significant. Three patients in ACDF group had hoarseness of voice due to recurrent laryngeal nerve palsy and there were no fresh permanent neurological deficits in any patients of PCL group over a follow-up period of 36 months. The average postoperative hospital stay was 5 days in ACDF group and 3 days in PCL group. The average intraoperative blood loss was <50 ml in ACDF group and 650 ml in PCL group. The need of analgesic for pain arising from bone graft site in ACDF group was comparable with operative site pain in PCL group. Conclusions: PCL is a simple approach, yields gratifying results, and is a promising alternative in selected cases of cervical monoradiculopathy due to disc prolapse.